2021
DOI: 10.3389/fnana.2020.570058
|View full text |Cite
|
Sign up to set email alerts
|

Indolaminergic System in Adult Rat Testes: Evidence for a Local Serotonin System

Abstract: Serotonin (5-HT) is member of a family of indolamine molecules that participate in a wide variety of biological processes. Despite its important role in the regulation of local blood systems, little is known about the physiological function of 5-HT in reproductive organs, its functional implications, and its role in the reproduction of mammals. In the present work, we evaluated the localization and distribution of 5-HT (using histochemical analysis of indolamines) and different components of the serotoninergic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…The presence of 5-HT3 A in the sperm acrosome in control rabbits is in agreement with the finding of these receptors in other mammal species including humans [ 32 , 51 , 52 ] and reinforces the hypothesis that these cation-selective 5-HT-gated ion channels could be important for the sperm movement when they are in the female tract. The presence of these receptors in the interstitial zone was unexpected, and in a previous work of the description of indoleaminergic elements in normal rat testes 5-HT3 A , it was found in the seminiferous tubules but not interstitial space [ 51 ], but in an earlier work, Dufau et al (1993) found that 5-HT could modulate the corticotropin-releasing factor (CRF) through 5HT 2 receptors in Leydig cells [ 30 ]. Although 5HT3 agonists were not able to induce the release of CRF, it is possible that 5-HT3 A receptors could participate in other cellular processes, but further experiments are required to test this statement.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The presence of 5-HT3 A in the sperm acrosome in control rabbits is in agreement with the finding of these receptors in other mammal species including humans [ 32 , 51 , 52 ] and reinforces the hypothesis that these cation-selective 5-HT-gated ion channels could be important for the sperm movement when they are in the female tract. The presence of these receptors in the interstitial zone was unexpected, and in a previous work of the description of indoleaminergic elements in normal rat testes 5-HT3 A , it was found in the seminiferous tubules but not interstitial space [ 51 ], but in an earlier work, Dufau et al (1993) found that 5-HT could modulate the corticotropin-releasing factor (CRF) through 5HT 2 receptors in Leydig cells [ 30 ]. Although 5HT3 agonists were not able to induce the release of CRF, it is possible that 5-HT3 A receptors could participate in other cellular processes, but further experiments are required to test this statement.…”
Section: Discussionsupporting
confidence: 89%
“…In sharp contrast, the presence of immature gonocytes and the absence of sperm in COI rabbits are consistent with a failure in spermatogenesis. It has been previously reported that TPH1 is expressed in mature sperm, at least in horses, rats, and humans [ 32 , 51 , 52 ]. On the other hand, the catabolic monoamine oxidase A (MAO A ) enzyme was found in the Leydig cells, spermatogonia, and spermatocytes of control rabbits and across all cell layers of seminiferous tubules but not in Leydig cells in COI rabbits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Raman spectra indicated a robust decline in the concentration of tryptophan and hydroxyproline in a time-dependent manner. Tryptophan is implicated in testosterone production and spermatogenesis in testes 27 . Thus, a reduced expression of tryptophan is consistent with histopathological disruption, including the reduced density of spermatozoa in the HU testes.…”
Section: Discussionmentioning
confidence: 99%